Curative Embolization with Onyx of Dural Arteriovenous Fistulas with Cortical Venous Drainage - van Rooij, W.J. (AJNR Am J Neuroradiol, 2010)
BACKGROUND AND PURPOSE: Dural fistulas with cortical venous drainage often present with hemorrhage or neurologic deficit, and prompt treatment is indicated. Occlusion of the draining vein by endovascular techniques or surgical disconnection is considered curative. We present our first endovascular experience with use of Onyx via the arterial route in these aggressive fistulas. MATERIALS AND METHODS: Between October 2008 and October 2009, 8 consecutive patients with a dural fistula with exclusive cortical venous drainage were treated with Onyx. Three patients presented with hemorrhage; 3, with hemianopsia; 1 with bruit; and 1 after incomplete coil occlusion of a benign sigmoid sinus dural fistula. Fistula location was the sigmoid sinus segment in 4, the occipital area in 2, the cavernous sinus in 1, and the torcula in 1. RESULTS: In all 8 patients, it was possible to occlude the proximal venous site of the fistula with Onyx via arterial feeders, resulting in complete cure in all. In 6 patients, a prolonged (17- to 29-minute) single middle meningeal artery injection was sufficient to occlude the venous site of the fistula with retrograde occlusion of other arterial feeders; in the other 2 patients, 2 injections in supplying arteries were needed. Follow-up angiograms after 6–12 weeks confirmed lasting complete occlusion of the fistulas. All patients were clinically cured, there were no complications. CONCLUSIONS: In this small series, curative embolization of dural fistulas with exclusive cortical venous drainage by using Onyx via the arterial route was possible in all patients.